2019
DOI: 10.1002/dneu.22682
|View full text |Cite
|
Sign up to set email alerts
|

Song Feature Specific Analysis of Isolate Song Reveals Interspecific Variation in Learned Components

Abstract: Studies of avian vocal development without exposure to conspecific song have been conducted in many passerine species, and the resultant isolate song is often interpreted to represent an expression of the genetic code for conspecific song. There is wide recognition that vocal learning exists in oscine songbirds, but vocal learning has only been thoroughly investigated in a few model species, resulting in a narrow view of birdsong learning. By extracting acoustic signals from published spectrograms, we have ree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 74 publications
(82 reference statements)
2
12
0
Order By: Relevance
“…It should be recognized that effects of social isolation and social crowding have also been recorded in non-mammalian social species, including in insects (Wang et al, 2008;Lihoreau et al, 2009;Ueda and Wu, 2009;Stevenson and Rillich, 2013), fish (Halperin and Dunham, 1993;Brandão et al, 2015;Shams et al, 2015), and birds (Apfelbeck and Raess, 2008;Banerjee and Adkins-Regan, 2011). Notably, a recent study found immediate effects of social isolation in the expression of several immediate early genes in the forebrain of an avian species (George et al, 2019), a finding which has implications for the field of vocal learning, which historically relies on the isolation of animals (Love et al, 2019). It is difficult to determine at present how much of the human response to social density stressors is unique to humans; do we find similar responses among distantly-related taxa that show similarity in social systems, or does genetic relatedness play a more important role in determining how the CNS modulates behavior in response to social density?…”
Section: Discussionmentioning
confidence: 99%
“…It should be recognized that effects of social isolation and social crowding have also been recorded in non-mammalian social species, including in insects (Wang et al, 2008;Lihoreau et al, 2009;Ueda and Wu, 2009;Stevenson and Rillich, 2013), fish (Halperin and Dunham, 1993;Brandão et al, 2015;Shams et al, 2015), and birds (Apfelbeck and Raess, 2008;Banerjee and Adkins-Regan, 2011). Notably, a recent study found immediate effects of social isolation in the expression of several immediate early genes in the forebrain of an avian species (George et al, 2019), a finding which has implications for the field of vocal learning, which historically relies on the isolation of animals (Love et al, 2019). It is difficult to determine at present how much of the human response to social density stressors is unique to humans; do we find similar responses among distantly-related taxa that show similarity in social systems, or does genetic relatedness play a more important role in determining how the CNS modulates behavior in response to social density?…”
Section: Discussionmentioning
confidence: 99%
“…It is this independence, which allows the two aspects of one signal to evolve separately from one another. Song rhythm is produced through song-associated respiratory patterning, which is thought to be largely innate in many species (Araki et al, 2016;Love et al, 2019;Marler & Sherman, 1983Thorpe, 1958), while syllable morphology arises through syringeal motor gesturing, which is more likely to be learned to a greater extent (Ali et al, 2013;Love et al, 2019;Marler & Sherman, 1983.…”
Section: Discussionmentioning
confidence: 99%
“…It is thought that learning increases rates of trait change through a higher copy‐error rate compared with the absence of learning, and song learning has been implicated in the rapid diversification of vocal learning songbirds (Lachlan & Servedio, 2004). However, it remains difficult to form hypotheses of precisely how vocal learning influences song evolution, because details of the learning process vary (e.g., species differences in tutor–tutee relationships, timing of the sensitive period) and substantial interspecific variation exists in which features of song must be learned (Love et al., 2019),…”
Section: Introductionmentioning
confidence: 99%
“…A second and strong possibility is that the observed differences reflect the respective song development in suboscines and oscines (e.g., Gahr, 2000;Jarvis, 2004). Tyrannids develop song innately and are not vocal learners (Kroodsma, 1984(Kroodsma, , 1989Kroodsma & Konishi, 1991), whereas almost all oscines appear to rely on learning for at least some aspects of their song (e.g., Hultsch & Todt, 2008;Kroodsma, 1983;Love et al, 2019). The striking difference in frequency ranges (means differ by 3,100 Hz) of the entire song syllable repertoire (Figure 3a) between tyrannids and emberizids/passerellids may be explained by oscine vocal learning.…”
Section: Discussionmentioning
confidence: 99%